How active are young cardiac device patients? Objective assessment of activity in children with cardiac devices. Issue 11 (10th October 2017) - de la Uz, Caridad M.; Burch, Ashley E.; Gunderson, Bruce; Koehler, Jodi; Sears, Samuel F.
Abstract: Background: The daily activity of pediatric patients with implantable cardiac devices provides behavioral evidence of functional outcomes. Modern devices provide continuous accelerometer data that are sensitive to movement, but normative values have not been published for pediatric activity rates. This study provides the first normative accelerometer data on activity rates in a large sample of pediatric cardiac device patients. Methods: Patients were between 3 and 18 years old (N = 1, 905) and implanted with a cardiac device from a single device company, and enrolled in remote monitoring. Results: The median age at implant was 14 years (interquartile range = 12–16); 61.3% were male. Data for 4 weeks were extracted from a company database at 53 weeks postimplant and an average of daily activity was calculated. Daily average activity for all patients was 5.4 hours (standard deviation  =  2.0). In a multivariate analysis, increased level of activity was associated with: being male, having a pacemaker versus implantable cardioverter defibrillator (ICD), epicardial device location, rate response turned off, having experienced a shock, and younger age. Conclusions: These results provide the first baseline data of physical activity in children with implanted cardiac devices and provide a clinical guide to physical activity assessment in this population. Further, our data suggest physical activity in children with implantable cardiac devices may differ based on demographic variables, device type, device location, indication for implantation, and history of ICD shock.